An Secured Intrusion Detection System Integrated with the Conditional Random Field For the Manet Network - Rexhepi, Burhan R.; Kumar, Avneesh; Gowtham, M. S.; Rajalakshmi, R.; Paikaray, Divya; Adhikari, Pronab Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
MANET is a wireless network that lacks infrastructural support. Most operations they perform are coordinated between nodes because of their limited transmission range. Assess the secure MANET routing protocol in a malicious environment. However, in the MANET environment security is an important constraint that affects the data transmission rate and cause data loss. This paper developed an Intrusion Detection System Conditional RandomField (IDS – CRF) model for security. The developed model uses the hashing function integrated with the Conditional Random Field model. The IDS – CRF model uses the label sequences for data security in the MANET environment. The model uses the DSR protocol with the discriminative field to process the secure data in the MANET. The proposed IDS-CRF model uses the hashing function for improved data transmission security in the MANET environment. The performance of the proposed IDS – CRF model is comparatively examined with the conventional DSR protocol. The comparative analysis expressed that the proposed IDS – CRF model achieves the 4% reduction in the delay and 2% reduction in the routing overhead. Similarly, the proposed IDS – CRF model achieves the 4% reduced energy consumption. In terms of the Packet delivery ratio and throughput the proposed IDS – CRF model achieves the 4% - 6% improved performance than DSR model.